A .NET application searching for deleted, modified and added statements into control programs of the KUKA industrial welding robot during its testing - Košťál, Igor, 1962-
Aplikácia .NET pre zefektívnenie a zrýchlenie aktivít robotov pri zvázačských procesoch v softvéroch KUKA.